Justification of the parameters and operating modes of the disinfecting system. Issue 1 (February 2021) - Levshin, A; Gasparyan, I; Sychev, V; Bitsoev, B; Shchigolev, S
Abstract: Increasing yields is an important task for our country. This is possible due to removing the tip of the shoot, which stimulates the potential of the plant itself, and such products can be sold as organic since no other chemicals are used to increase yields. When the shoot tip is removed, a wound is formed through which pathogens can enter. To reduce the likelihood of plant contamination, the device provides a system for applying a disinfectant solution (hydrogen peroxide) to the knife blade. The settings of the injector are taken into account. When choosing a spray gun, it is necessary to take into account the average working pressure, equal to P = 0.28 MPa, which provides a solution flow rate щa Q = 0.8 l min -1 with a nozzle diameter of 0.1 mm. These requirements can be met by spray guns of caliber 04 or 05. At a spray angle of 800, the recommended spray angle is 300; the mounting distance is 0.3 m below the plane of rotation of the cut-off wheel. The initial flow rate of the liquid of 17.33 m s -1 will provide stable droplet formation, providing the recommended dispersion of the solution of 150-200 microns.